Penerapan Metode Cross Group Discussion Untuk Meningkatkan Kreativitas Dan Hasil Belajar Siswa SMPN 4 Liukang Tangaya - Musdalifah; Muh Yunus; Elpisah (Cetta: Jurnal Ilmu Pendidikan, 2022)
The purpose of the study is to know the application of methods cross group discussion to increase creativity and learning outcomes of SMPN 4 Liukang Tangaya. Research is class action research. Observation and test data collection techniques. Analytical descriptive data analysis techniques. Research shows that 1) The percentage of student creativity increases drastically with each cycle, with student creativity falls into a sufficient category in cycle I and develops into a good category in cycle II. 2) Student learning outcomes each cycle increased by 100%, completion rate in cycle I 28.6%, average learning outcomes 70.71%, completion rate in cycle I 28.6%, cycle II completion rate 100%, with average learning outcomes 93.57%.